2010
DOI: 10.1590/s0004-27302010000800005
|View full text |Cite
|
Sign up to set email alerts
|

Congenital leptin deficiency: diagnosis and effects of leptin replacement therapy

Abstract: SUMMARY To describe our 10-year experience in treating leptin-deficient humans. Three adults and one boy presented with childhood-onset morbid obesity, hypogonadism and family history of obesity and early death. Serum leptin was inappropriately low. A recessive C105T leptin gene mutation was identified. Metabolic and endocrine assessments were conducted, before and while on and off leptin. The adults’ body mass index decreased from 51.2 ± 2.5 to 29.5 ± 2.8 kg/m2. Serum lipids normalized, insulin resistance dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 35 publications
(52 reference statements)
2
56
0
2
Order By: Relevance
“…Consistent with the study by Glasow et al, 31 we demonstrated that human and rat adrenal glands coexpress leptin receptors and CYP11B2, in zona glomerulosa cells, implying that leptin could regulate the function of zona glomerulusa cells. In agreement with the literature reporting low aldosterone levels in obese individuals 32,33 and animals [34][35][36][37][38][39] deficient in leptin receptors, we reported that leptin deficiency in ob/ob mice, deletion in leptin receptor in db/db mice, or nonfunctional mutation of the leptin receptors in obese Zucker rats blunted obesity-induced increases in adrenal CYP11B2 expression and plasma aldosterone levels. These data support a role for leptin and leptin receptors in obesity-mediated increases in plasma aldosterone levels and minimize the contribution of obesity per se in the control of aldosterone secretion.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the study by Glasow et al, 31 we demonstrated that human and rat adrenal glands coexpress leptin receptors and CYP11B2, in zona glomerulosa cells, implying that leptin could regulate the function of zona glomerulusa cells. In agreement with the literature reporting low aldosterone levels in obese individuals 32,33 and animals [34][35][36][37][38][39] deficient in leptin receptors, we reported that leptin deficiency in ob/ob mice, deletion in leptin receptor in db/db mice, or nonfunctional mutation of the leptin receptors in obese Zucker rats blunted obesity-induced increases in adrenal CYP11B2 expression and plasma aldosterone levels. These data support a role for leptin and leptin receptors in obesity-mediated increases in plasma aldosterone levels and minimize the contribution of obesity per se in the control of aldosterone secretion.…”
Section: Discussionsupporting
confidence: 93%
“…Leptin also plays important roles on lipid and glucose metabolism, the gonadal, adrenal, somatotropic and thyroid axes, sympathetic tone, biomarkers of cardiovascular disease, immunity, inflammation, and brain structure and function (5,6,(32)(33)(34). In humans, leptin deficiency is observed in cases of hypothalamic amenorrhea, anorexia nervosa, genetic deficiency due to mutations in the leptin gene, and LS.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important metabolic regulator responsible for not only controlling food intake and energy expenditure, but also for maintaining glucose, insulin and lipid homeostasis (5,6). Impaired leptin action, due to leptin resistance or leptin deficiency, results in several metabolic abnormalities such as insulin resistance, hyperinsulinemia, diabetes, and hypertriglyceridemia, which are similar to those that are observed in LS.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin levels are directly correlated with fat mass and are elevated in obese patients, who are also leptin resistant. Leptin deficient mice and humans are severely obese and have several metabolic and endocrine altera tions, such as hyperglycemia, insulin resistance, hyper triglyceridemia, hypogonadotropic hypogonadism, and central hypothyroidism (6,7).…”
Section: Introductionmentioning
confidence: 99%